Diabetic foot: Evaluation and preventive practices of nurses in family health strategy - Eleutério, Talita Aparecida Duarte; Tavares, Bárbara Primavera; Saccomann, Izabel Cristina Ribeiro; Camargo, Tamara Carolina de (Seven Editora, 2023)
Systematic evaluation of the feet is essential in identifying risk factors and reducing the chances of ulceration and amputation. The objectives of this study were to evaluate the preventive practices performed by nurses during the nursing consultation and to examine the feet of diabetic patients. This is a quantitative study carried out in the Family Health Strategy Units, in the interior of São Paulo. For data collection, a structured script was used to evaluate the diabetic patient and a questionnaire regarding the preventive practices used by the nurse during the nursing consultation. The most frequent alterations presented by the patients were: inadequate shoes (65%), ineffective hydration (60%), skin alteration (95%), signs indicative of mycosis (55%), loss of protective sensitivity (35%) and loss of vibratory sensitivity (45%). The preventive practices performed by the nurses were: assessment of nutritional status (62.5%), measurement of systemic blood pressure (43.8%), glycemic control (87.5%), skin inspection (62.5%), nail trimming (50%), type of footwear (62.5%). Most nurses did not perform the monofilament test (81.2%) or the vibratory sensitivity test (93.7%). Nurses play an important role in the early detection of risk factors, but it is not yet a practice incorporated by everyone. DOI:https://doi.org/10.56238/sevened2023.006-066